2019
DOI: 10.2298/jas1903279b
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investment analysis of small-scale broiler and layer enterprises in Osun State, Nigeria

Abstract: The study investigated the investment patterns, costs and return structures of the layer and broiler production in Osun State, Nigeria. It also compared their net present value in the study area to determine their investment returns. A multistage sampling technique was employed in selecting respondents for the study. Primary data were collected from 180 broiler and layer farms, comprising 90 broiler farms and 90 layer farms from six local governments in Osun State using a structured questionnaire. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Vlaović Begović et al of purchasing 10 hectares of agricultural land for corn cultivation using several dynamic methods of capital budgeting with the following results and conclusion: the net present value of the investment is 43,415 euros, the internal rate of return is 9.91%, the profitability index is 1.22, which imply that this investment should be implemented. Baruwa and Fabode (2019) evaluated the investments in the layer and broiler production with results that showed that both investments are acceptable but the investment in layer production has a higher, positive net present value and the value of the internal rate of return compared to the investment in the production of broilers, as well as a shorter discounted payback period. Lopes Santos et al (2020) investigated two soybean cultivation systems using three different price scenarios and discounted cash flows of the investment (which includes the net present value method), as well as cost-volume-profit analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vlaović Begović et al of purchasing 10 hectares of agricultural land for corn cultivation using several dynamic methods of capital budgeting with the following results and conclusion: the net present value of the investment is 43,415 euros, the internal rate of return is 9.91%, the profitability index is 1.22, which imply that this investment should be implemented. Baruwa and Fabode (2019) evaluated the investments in the layer and broiler production with results that showed that both investments are acceptable but the investment in layer production has a higher, positive net present value and the value of the internal rate of return compared to the investment in the production of broilers, as well as a shorter discounted payback period. Lopes Santos et al (2020) investigated two soybean cultivation systems using three different price scenarios and discounted cash flows of the investment (which includes the net present value method), as well as cost-volume-profit analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research showed that the net present value of the investment is 43,415 euros, the internal rate of return is 9.91%, and the profitability index is 1.22, and they concluded that the investment should be implemented. Baruwa and Fabode (2019) investigated the investments, as well as a structure of costs and returns of the layer and broiler production investments in the state of Osun, Nigeria. The results of the research showed that the investment in layer production has a higher, positive net present value and the value of the internal rate of return in relation to the investment in the production of broilers, as well as a shorter discounted payback period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This country has the biggest layers and broilers industry and provides a promising business opportunity for technology providers, investors, and business experts [3]. Meanwhile, in other developing countries, such as Nigeria, poultry has a significant position due to its superiority in resulting a massive economic growth, mainly business opportunities for low-economic groups (4]. In addition, the Government of Pakistan is determined to improve its society's life quality, and prevents hunger and lack of nutrition by designing a productive, efficient, and economically-beneficial agriculture sector [5].…”
Section: Introductionmentioning
confidence: 99%